Role of selenium in relieving oxidative stress in cardiac muscle on fluoride toxicity - Dr.SUNITHA NARENDRULA; Dr. SHOBHA MOHAMMED; Dr. MUJAHID MOHAMMED; Dr.SARITHA SATKUR (International Journal of Pharma and Bio Sciences, 2018)
Selenoprotein rich selenium exhibits its antioxidant property by offering protection against the reactive oxygen species (ROS). It is well known fact that excesses of fluoride consumption above the permissible level may cause increase level of ROS which further causes cellular damage. Current experiment was designed to investigate the ameliorative role of selenium on the myocardium of wistar rat heart when exposed to chronic fluoride toxicity. Adult albino wistar rats were fed with the 200 ppm of fluoride for 90 days and protection of selenium was offered for 20days. Decreased antioxidant enzyme GSH and increased malondialdehyde levels may be related to oxidative damage in the myocardium of wistar rats. Fluoride treatment significantly increased the lipid peroxidation and decreased the activity of antioxidant enzymes, especially the glutathione level in ventricle of the heart. Biochemical changes were supported by the histological observations which also revealed that chronic exposure to fluoride causes damage to the myocardium. Fluoride exposed group II is stastically significant on control group I (P<0.05) and selenium supplemented group III for 20 days has reversed the peroxidative changes in myocardium which was stastically significant on fluoride group II (P<0.05). Results of the current study may be taken as an index of cardio-toxicity in wistar rats exposed to high levels of fluoride water. Further, oral supplementation of selenium not only inhibits the oxidative stress but also enhances the activities of antioxidant enzymes. Administration of antioxidants during fluoride exposure may significantly overcome the cardiac fluoride toxicity and therefore may be adopted as therapeutic strategy for the people living in fluoride endemic zones.